The last shot - Grothaus, Steve; Jones, Lonzo; Dunn, Jeff; Meridian education Corporation (Lawrenceville, NJ : Meridian Education Corporation, 2000)
This timely and emotionally charge dramatization examines the growing problem of violence in our schools
Title from title screen
Cast: Cast: Evan Fowler, Jeff Reno, Alan Bowmar Jones, Chris Lingan, Suzanne Laino, Gerard Barnes, Lonzo Jones
DVD format
Keywords: School shootings -- United States; School violence -- United States; High school students -- United States -- Attitudes